Microbial Community of High Arsenic Groundwater in Agricultural Irrigation Area of Hetao Plain, Inner Mongolia - Wang, Yanhong; Li, Ping; Jiang, Zhou; Sinkkonen, Aki; Wang, Shi; Tu, Jin; Wei, Dazhun; Dong, Hailiang; Wang, Yanxin (Frontiers in Microbiology, 2016)
Microbial communities can play important role in arsenic release in groundwater aquifers. To investigate the microbial communities in high arsenic groundwater aquifers in agricultural irrigation area, 17 groundwater samples with different arsenic concentrations were collected along the agricultural drainage channels of Hangjinhouqi County, Inner Mongolia and examined by illumina Miseq sequencing approach targeting the V4 region of the 16S rRNA gene. Both principal component analysis and hierarchical clustering results indicated that these samples were divided into two groups (high and low arsenic groups) according to the variation of geochemical characteristics. Arsenic concentrations showed strongly positive correlations with NH4+ and TOC. Sequencing results revealed that a total of 329-2823 OTUs were observed at the 97% OTU level. Microbial richness and diversity of high arsenic groundwater samples along the drainage channels were lower than those of low arsenic groundwater samples but higher than those of high arsenic groundwaters from strongly reducing areas. The microbial community structure in groundwater along the drainage channels was different from those in strongly reducing As-rich aquifers of Hetao Plain and other high As groundwater aquifers including Bangladesh, West Bengal and Vietnam. Acinetobacter and Pseudomonas dominated with high percentages in both high and low arsenic groundwaters. Alishewanella, Psychrobacter, Methylotenera and Crenothrix showed relatively high abundances in high arsenic groundwater, while Rheinheimera and the unidentified OP3 were predominant populations in low arsenic groundwater. Archaeal populations displayed a low occurrence and mainly dominated by methanogens such as Methanocorpusculum and Methanospirillum. Microbial community compositions were different between high and low arsenic groundwater samples based on the results of principal coordinate analysis and co-inertia analysis. Other geochemical variables including TOC, NH4+, ORP and Fe might also affect the microbial composition.